2022
DOI: 10.3389/fneur.2022.925748
|View full text |Cite
|
Sign up to set email alerts
|

Short Report of Longitudinal CGRP-Measurements in Migraineurs During a Hypoxic Challenge

Abstract: BackgroundCalcitonin gene related peptide (CGRP) plays a key role in the pathophysiology of migraine and is therefore considered a potential biomarker for primary headache disorders. The challenge remaining is establishing standardized protocols for its assessment in various extracellular compartments and identifying pathological situations associated with an increase in CGRP.MethodsWe performed longitudinal measurements of CGRP plasma levels in 30 volunteers with the diagnosis of episodic migraine with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…Using this standardized ELISA based approach, in a longitudinal measurement of CGRP during a normobaric hypoxic challenge in migraine patients, we found elevated CGRP levels with increasing duration of the hypoxic challenge ( Frank et al, 2022 in press).…”
Section: Course Of Migraine Related Biomarkers Under Hypoxiamentioning
confidence: 95%
“…Using this standardized ELISA based approach, in a longitudinal measurement of CGRP during a normobaric hypoxic challenge in migraine patients, we found elevated CGRP levels with increasing duration of the hypoxic challenge ( Frank et al, 2022 in press).…”
Section: Course Of Migraine Related Biomarkers Under Hypoxiamentioning
confidence: 95%
“…Increased CGRP expression in the TG was not persistent in tongue neuropathic pain models [ 21 , 34 ]. Prolonged hypoxia was sufficient to increase CGRP plasma levels in patients with migraine [ 18 ]. Therefore, it can be inferred that hypoxia has a substantial impact on CGRP upregulation in the TG.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that oral appliance treatment for OSA may be beneficial for treating headaches in patients with OSA [ 15 ], whereas hypoxia can trigger migraine-like headaches in patients and healthy individuals [ 16 ]. Calcitonin gene-related peptide (CGRP) levels in venous blood, but not substance P, are elevated during acute migraine attacks [ 17 ] and after hypoxic challenge, akin to migraine attacks [ 18 ]. The density of CGRP-positive fibers innervating the oral mucosa is increased in patients with OSA [ 19 ], which suggests that CGRP is a critical factor causing orofacial pain in OSA-like conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bei 2 Patienten war es die erste Aura überhaupt [47]. Bei diesen Patienten wurden die venösen Calcitonin Gene-Related Peptide (CGRP)-Spiegel vor und nach einer 6-stündigen normobaren Hypoxie (Sauerstoffpartialdruck 4500 m Seehöhe) [48] bestimmt. Im Gruppenmittel stiegen die CGRP-Spiegel im Verlauf der Hypoxie an, wobei eine große interindividuelle Streuung bestand.…”
Section: Untersuchungen Zum Höhenkopfschmerzunclassified